2019
DOI: 10.4236/scd.2019.91001
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Mesenchymal Stem Cells as Feeder Cells Facilitate the Cultivation of Primordial Germ Cells from Circulating Blood and Gonadal Ridge

Abstract: Long-term maintenance of chicken primordial germ cells (PGCs) in vitro has tremendous potential for transgenic chicken production. Feeder cells are essential for the establishment and culture of chicken PGCs in vitro. Buffalo rat liver (BRL) cells are the most commonly used feeder cells for PGCs culture; however, this feeder layers from other animal species usually cause immunogenic contaminations, compromising the potential of PGCs in applications. Therefore, we tested chicken source mensenchymal stem cell (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…PGC proliferation in vitro depends upon the feeder cells having a powerful capacity to proliferate and secrete cytokines [52,53]. The authors [54] reported that feeder cells can promote proliferation of circulating blood PGCs (cPGCs) and gonadal PGCs (gPGCs) in vitro and that they have the characteristics of an effective feeder layer. Several studies have shown that an MSC-feeder layer ensures all conditions for human-induced pluripotent stem cell (hiPSC), human embryonic stem cell (hESC), and mouse embryonic stem cell (mESC) proliferation and expansion and, moreover, while maintaining cell pluripotency [55][56][57].…”
Section: Feeder Cells Layermentioning
confidence: 99%
See 1 more Smart Citation
“…PGC proliferation in vitro depends upon the feeder cells having a powerful capacity to proliferate and secrete cytokines [52,53]. The authors [54] reported that feeder cells can promote proliferation of circulating blood PGCs (cPGCs) and gonadal PGCs (gPGCs) in vitro and that they have the characteristics of an effective feeder layer. Several studies have shown that an MSC-feeder layer ensures all conditions for human-induced pluripotent stem cell (hiPSC), human embryonic stem cell (hESC), and mouse embryonic stem cell (mESC) proliferation and expansion and, moreover, while maintaining cell pluripotency [55][56][57].…”
Section: Feeder Cells Layermentioning
confidence: 99%
“…Several studies have shown that an MSC-feeder layer ensures all conditions for human-induced pluripotent stem cell (hiPSC), human embryonic stem cell (hESC), and mouse embryonic stem cell (mESC) proliferation and expansion and, moreover, while maintaining cell pluripotency [55][56][57]. MSCs have potential as a feeder cell layer in vitro to provide for expansion of chicken PGCs [54]. Further research is needed to analyze the potential interactions of MSCs via MSC-secreted cytokines with the different chicken cell types.…”
Section: Feeder Cells Layermentioning
confidence: 99%
“…MSCs are plastic adherent and positive for cluster of differentiation ( CD ) CD73, CD90, CD105 surface antigens and also characterized by the lack of proteins expression such as CD45, CD34 ( Sacchetti et al, 2007 ; Teresa Conconi et al, 2011 ; Lin et al, 2013 ; Cruz and Rocco, 2020 ). In chickens, MSCs can be used as feeder layer for primordial germ cells ( PGCs ) ( Li et al, 2019 ), and thus support treatment for immunosuppressive disorder, such as infectious bursal disease virus ( IBDV ), which does not proliferate in chicken fibroblast cells ( Majumdar et al, 1998 ). Moreover, they should be useful tool for examining underlying effects of vitamin D3, calcitriol (1,25-(OH)2D3) administration as well as a promising approach in immunomodulatory properties through the coculture in vitro with the pathogens ( Gil et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%